Arthrodesis of ankle joint. Biomechanical aspects and algorithm of choice of methods of fixation - Omelchenko, Taras; Buryanov, Oleksandr; Lyabakh, Andriy (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
Objective: to improve the results of ankle joint arthrodesis by applying of biomechanical modification of the surgery technique and a differentiated approach to choice of methods of fixation. Methods: 348 patients (192 males, 156 females, middle age) were studied. Average age was (48.5 ± 3.8) years. In the main group (n1 = 176) modified method of arthrodesis of the ankle joint and differentiated approach for choosing means of fixation was applied, in the control group (n2 = 172) — t raditional m ethods of arthrodesis were used. Results: in the main group in 164 patients (93 %) the arthrodesis proved to be effective, the mean time of bone fusion was (8.9 ± 0.4) weeks. In the control group bone fusion was observed in 138 patients (79 %) in (11.5 ± 0.9) weeks postoperatively. In (3.4 ± 1.8) years when we evaluated results according to AOFAS in the main group, the average index for the posterior part of the foot was (78.2 ± 1.2) points, for the middle part — (81.3 ± 1.3), which corresponds to good functional results at absolute absence of motion in ankle joint. In the control group, the average index of AOFAS for the posterior part of the foot was (57.1 ±1.3) points, for the middle — (53.7 ± 1.4). In the main group compare to control group we have revealed a decreasing in total time of foot weight bearing by 17.8 %, increasing in time of rolling over the heel (average (23.8 ± 0.8) %), reduction of time of rollover through the anterior part to (27.1 ± 1.2) % and moderate elevation of the interjoging period (49.1 ± 1.2) %. Decreasing of strength impulse of the vertical component in the main group (3608 ± 2.4) compare to the control group (3982 ± 3.6) indicated to decreasing in the energy intensity of walking when we used a modified resection technique for arthrodesis. Conclusions: modified method for resection arthrodesis of ankle joint is shown to be better than traditional one. That is confirmed by functional, biomechanical and X-ray studies.